Pengalaman Lanjut Usia dalam Menghadapi Situasi Paska Tsunami - Febri Christian; Mustikasari Mustikasari (Jurnal Keperawatan Silampari, 2023)
This study aims to explore the experiences of older people in dealing with post-tsunami situations. The research method used is a qualitative method with a descriptive approach. The study results obtained five main themes: the feelings that emerged during the tsunami, the impact of the tsunami, efforts to deal with post-tsunami trauma, sources of support for participants, and how to build self-confidence after the tsunami. In conclusion, the tsunami was a disaster that caused fear, sadness, anxiety, and trauma to those who experienced it. In addition to negative feelings, the tsunami caused the loss of lives of loved ones and property for the victims. Efforts were made to eliminate trauma and build self-confidence (self-efficacy) by telling each other stories to neighbors, praying and surrendering, and being optimistic about living a post-Tsunami life because of family members who survived. Keywords: Elderly, Post Tsunami, Experience